Evaluation of nanosilica effects on concrete submitted to chloride ions attack - Zanon, Thiago; Schmalz, Rosana; Ferreira, Fernanda Giannotti da Silva (Revista ALCONPAT, 2018)
The present paper studied the influence of nanosilica dispersed on superplasticizer, and its combined effect with silica fume, on different concrete properties. Compressive strength, tensile strength by diametrical compression and water absorption by capillarity tests, as well as accelerated durability tests against chloride ions were carried out. The results indicated that the isolated nanosilica addition (0.1 to 0.5%) did not improve the concretes in any of the tests performed. However, for the contents of 0.5 and 0.7% of nanosilica combined with 10% of silica fume, there was an increase in compressive strength, reduction of capillary absorption and reduction of the chlorides penetration.